Cyclic Dinucleotides in Oral Bacteria and in Oral Biofilms - Gürsoy, Ulvi K.; Gürsoy, Mervi; Könönen, Eija; Sintim, Herman O. (Frontiers in Cellular and Infection Microbiology, 2017)
Oral cavity acts as a reservoir of bacterial pathogens for systemic infections and several oral microorganisms have been linked to systemic diseases. Quorum sensing and cyclic dinucleotides, two “decision-making” signaling systems, communicate to regulate physiological process in bacteria. Discovery of cyclic dinucleotides has a long history, but the progress in our understanding of how cyclic dinucleotides regulate bacterial lifestyle is relatively new. Oral microorganisms form some of the most intricate biofilms, yet c-di-GMP and c-di-AMP signaling have been rarely studied in oral biofilms. Recent studies demonstrated that, with the aid of bacterial messenger molecules and their analogs, it is possible to activate host innate and adaptive immune responses and epithelial integrity with a dose that is relevant to inhibit bacterial virulence mechanisms, such as fimbriae and exopolysaccharide production, biofilm formation, and host cell invasion. The aim of this perspective article is to present available information on cyclic dinucleotides in oral bacteria and in oral biofilms. Moreover, technologies that can be used to detect cyclic dinucleotides in oral biofilms are described. Finally, directions for future research are highlighted.